DETERMINAN PENDAPATAN ASLI DAERAH PROVINSI JAWA TENGAH - Prasetyo, Jalu Aldho Fajar (Jendela Inovasi Daerah, 2023)
The granting of regional autonomy is expected to give flexibility to regions to give flexibility to regions to take care of their own households. PAD is one of the regional revenues that reflects the level of regional independence. This study aims to analyze the effect of Government Expenditure, Population, and GRDP on he estimation model used the Error Correction Model (ECM) approach. As well as the results of the analysis of factors affecting the Local Own-Source revenue of Central Java, Government Expenditures have a significant effect in the short and long term for the Population to have a significant effect only in the short term while in the varibael of GRDP it has no significant effect in the short and long term.